Analisis Komprehensif terhadap Framework dan Alat Penetration Testing: Tren, Tantangan, dan Peluang: Comprehensive Analysis of Penetration Testing Frameworks and Tools: Trends, Challenges, and Opportunities - Fadhli, Mulkan (Institut Riset dan Publikasi Indonesia, 2024)
The crucial method in cybersecurity aimed at identifying and exploiting vulnerabilities in information systems to enhance security is known as Penetration Testing. The author attempts to present a comprehensive analysis of various penetration testing frameworks and tools, including OWASP, PTES, NIST SP 800-115, OSSTMM, and ISO 27001. Each framework has its distinct advantages and disadvantages, depending on the specific context and needs of the organization. Various penetration testing tools are evaluated based on their ability to detect and exploit vulnerabilities. Recent trends show an increase in the use of automated and AI-based tools to improve efficiency and accuracy. Open-Source Intelligence (OSINT) techniques are also becoming increasingly important in gathering initial information before penetration testing is conducted. However, there are significant challenges in penetration testing, including the complexity of modern systems, resource constraints, evolving threats, regulatory compliance, and the security of the testing tools themselves. These challenges are balanced by significant opportunities in the development of new tools, enhanced collaboration among the security community, increased awareness and investment in cybersecurity, education and training, and integration with DevSecOps methodologies. This article aims to provide in-depth and practical guidance for organizations in selecting and implementing the most suitable penetration testing frameworks and tools according to their needs. With a better understanding of the advantages, disadvantages, trends, challenges, and opportunities in penetration testing, organizations can significantly enhance their security posture..